Biofortification of Carrot (Daucus carota L.) with Iodine and Selenium in a Field Experiment - Smoleń, Sylwester; Skoczylas, Łukasz; Ledwożyw-Smoleń, Iwona; Rakoczy, Roksana; Kopeć, Aneta; Piątkowska, Ewa; Bieżanowska-Kopeć, Renata; Koronowicz, Aneta; Kapusta-Duch, Joanna (Frontiers in Plant Science, 2016)
The low content of iodine (I) and selenium (Se) forms available to plants in soil is one of the main causes of their insufficient transfer in the soil-plant-consumer system. Their deficiency occurs in food in the majority of human and farm animal populations around the world. Plant response to simultaneous fertilization with I and Se has not been investigated in depth. Neither I nor Se is essential for higher plants but can be considered as a beneficial element. The study (conducted in 2012–2014) included soil fertilization of carrot cv. “Kazan F1” in the following combinations: 1. Control; 2. KI; 3. KIO3; 4. Na2SeO4; 5. Na2SeO3; 6. KI+Na2SeO4; 7. KIO3+Na2SeO4; 8. KI+Na2SeO3; 9. KIO3+Na2SeO3. I and Se were applied twice: before sowing and as top-dressing in a total dose of 5 kg I•ha−1 and 1 kg Se•ha−1. No negative effects of I and Se fertilization were noted with respect to carrot yield. Higher accumulation and the uptake by leaves and storage roots of I and Se were obtained after the application of KI than KIO3, as well as of Na2SeO4 than Na2SeO3, respectively. Transfer factor values for leaves and roots were about a dozen times higher for Se than for I. Selenomethionine content in carrot was higher after fertilization with Na2SeO4 than with Na2SeO3. However, it was the application of Na2SeO3, KI+Na2SeO3 and KIO3+Na2SeO3 that resulted in greater evenness within the years and a higher share of Se from selenomethionine in total Se in carrot plants. Consumption of 100 g f.w. of carrots fertilized with KI+Na2SeO3 and KIO3+Na2SeO3 can supply approximately or slightly exceed 100% of the Recommended Daily Allowance for I and Se. Moreover, the molar ratio of I and Se content in carrot fertilized with KI+Na2SeO3 and KIO3+Na2SeO3 was the best among the research plots.